Application of GPS Technology to Evaluate the Quality of Public Transport - Bauer, M. (Acta Technica Jaurinensis, 2013)
This paper presents the importance of travel time researches in urban public transport. There were discussed the precision, scope and potential effects of the information, possible to get by different methods of measurements carried out with GPS receivers. Particular attention has been given to the author’s method of measurements. This method bases onto division of travel time (line or transport corridor) for detailed traffic processes: running time between two following stops, time of waiting for possibility of taking a position at the stop, alighting and boarding time and time of waiting for possibility to departure from stop. This kind of approach enables an overall evaluation of the public transport line quality. Application of the method was presented as an example of the public transport corridor in Cracow.